Poligami dalam Keluarga Kristen Di Desa Haumeni - Anthon Imanauel Selan; Mieke Yen Manu (Institut Agama Kristen Negeri Toraja, 2022)
In Christianity, polygamy is rejected because the essence of Christian marriage is monogamy, which is sacred and holy because a holy God formed it. This study aims to describe the practice of polygamy that occurs in Christian families in Haumeni Village. The method used in this research was a qualitative approach; the sampling technique was purposive sampling, and in-depth interviews were the data collection techniques. The results showed that the subject's polygamous factors were heredity, economic factors, and the feelings of the husband, who had changed. The impact of polygamy can be seen in the emotions, psychological conditions, differences in treatment and closed social relationships felt by the wives. The first wife experiences heartache, disappointment, and loneliness because the husband tends to love and care more for the second wife, who is able to give him offspring and fulfill his husband's wishes.Meanwhile, the impact experienced by the second wife is that she does not have a clear legal status from the government or the church. In addition, the subject also did not involve the family and the church in their actions of polygamy. Before becoming a church member, the church has not maximally handled the issue of polygamy, which is an old tradition of the local community. Abstrak: Dalam perspektif Kristen praktik poligami ditolak karena hakikat pernikahan Kristen adalah monogami yang sakral dan kudus sebab dibentuk oleh Allah yang Kudus. Penelitian ini bertujuan mendeskripsikan praktik poligami yang terjadi dalam keluarga Kristen di Desa Haumeni. Metode dalam penelitian ini adalah pendekatan kualitatif dan teknik samplingnya adalah purposive sampling. Teknik pengumpulan data dilakukan dengan wawancara mendalam. Hasil penelitian menunjukkan bahwa faktor berpoligami subjek adalah faktor keturunan, faktor ekonomi dan perasaan suami yang telah berubah. Adapun dampak praktik poligami terlihat dari perasaan, kondisi psikologis, perbedaan perlakuan dan hubungan sosial yang tertutup sangat dirasakan oleh para istri. Istri pertama mengalami sakit hati, kecewa dan kesepiaan karena suami cenderung lebih menyayangi dan perhatian pada istri kedua yang mampu memberinya keturunan dan memenuhi keinginan suami. Sedangkan dampak yang dialami oleh istri kedua adalah tidak memiliki status yang jelas secara hukum pemerintah maupun gereja. Selain itu, subjek juga tidak melibatkan keluarga dan gereja dalam tindakannya melakukan poligami. Gereja belum maksimal menangani persoalan poligami yang merupakan tradisi lama masyarakat setempat sebelum menjadi anggota gereja.